Analisis Strategi Pengelolaan Bank Sampah Sebagai Upaya Menambah Pendapatan Pondok Pesantren menggunakan Analisis SWOT - Haris Maknun, Muhamad; Khoerul Anam, Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Waste is the remains of daily human activities that are discarded from sources resulting from human and natural activities that do not have economic value. In 2020, total national waste will reach 67.8 million tons. This means that almost 270 million Indonesians produce around 185,753 tonnes of waste per day or 0.68 kilograms per individual. Al-Ihya Ulumaddin Islamic Boarding School is one of the boarding schools that requires education about waste and how to handle it. This is because waste handling has not yet reached the stage of the recycling or reuse process. Based on the description above, this research aims to analyze waste bank management strategies as an effort to increase business income at the Al-Ihya Ulumaddin Islamic Boarding School through the Waste Bank using the SWOT and Matrix Space methods. The research method in this study is a qualitative method and SWOT analysis which was carried out on the waste bank managers of the Al-Ihya Ulumaddin Islamic Boarding School, namely 10 people. The resulting conclusion is that there is participation and positive responses from students and the community. There is support from the students and the community. Analysis based on Matrix Space processing is in the Conservative quadrant, this can be seen in the support of facilities and infrastructure in carrying out managerial planning for waste management carried out by the AL Ihya Ulumadin Islamic boarding school. The recommendations proposed based on the SWOT analysis are building cooperatives, innovating recycled products with better quality, building networks, building communication with consumers, and innovating waste products.